Enhancing Arabic Vocabulary Mastery in Vocational Students: A Flashcard-Based Approach - Ramadhani, Muhammad Adam; Ammar, Farikh Marzuki (Indonesian Journal of Islamic Studies, 2024)
This study, conducted at a vocational school, aimed to enhance students' Arabic vocabulary proficiency utilizing flashcard-based methods, including the "What’s Missing" and "Slowly-Slowly" games. Employing a qualitative-quantitative approach with a One-Group Pretest-Posttest Design, 22 students out of a total population of 280 were sampled. Data collection encompassed teacher and student activity observations, alongside pretest and posttest assessments. Teacher activity exhibited 83.8% engagement, while student activity demonstrated 87.5%. Analysis of pretest and posttest scores revealed a noteworthy increase from 67.13 to 87.18. Statistical analysis using SPSS demonstrated a significant improvement (p < 0.05), affirming the effectiveness of flashcard media in elevating Arabic vocabulary mastery. These findings advocate for the integration of interactive, visual aids in language instruction, with implications for broader pedagogical practices. Highlight: Innovative Pedagogy: The study introduces a novel approach to language instruction using interactive flashcard-based methods, enhancing Arabic vocabulary acquisition in a vocational school setting. Engaging Activities: Both teacher and student engagement levels were high, indicating the effectiveness of the chosen methodology in fostering active participation and learning. Quantifiable Improvement: The significant increase in average scores from pretest to posttest underscores the positive impact of flashcard media on Arabic vocabulary mastery, as validated by statistical analysis using SPSS. Keyword: Arabic Vocabulary, Flashcard-Based Methods, Language Instruction, Vocational Education, Pedagogical Practices